Singularidades do futebol da cidade de Rio Grande/RS na década de 1930 - Lima, Fernando Godinho (2017)
Submitted by Márcio Ropke (ropke13marcio@gmail.com) on 2017-02-20T12:34:12Z No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Dissertação Fernando Lima 25-03-2014.pdf: 2558598 bytes, checksum: 13c979974329ee9ff4e9d52a99bf4a31 (MD5)